ANALISIS TERHADAP PERLINDUNGAN HUKUM BAGI NASABAH PENGGUNA ATM (SKIMMING KARTU ATM PADA MESIN ATM BANK X) - , Ronald Arthur Saiya, Prof. Dr. Nindyo Pramono S.H, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study was to analyze the validity of the provisions of the transactions from ATMs of Bank X and to analyze the protection that can be provided by law to protect the affected customer by card skimming in ATMs of Bank X. The methodology of this reserach is normative. Normative reserach is a law research which heads for investigate the fundamental of positive law in implementing on articles and law regulations. The research conducted is about stipulation of ATM transaction through ATM related with KUHPerdata, Banking Law, and Patronage of Consumer Law. The results of this study states that the legal protection of customer transactions at ATMs of Bank X is based on the Bank X's internal regulations ATM machines, namely Bank X using anti-skimming tools and anti-trapping cards so that customers canbe protected from the perpetrators of the crime, then by Undang â Undang Nomor 10 Tahun 1998 tentang Perubahan Undang â Undang Nomor 7 Tahun 1992 tentang Perbankan dalam Pasal 40 ayat (1) which states that the Bank is required to keep information about customers and their savings, and by Undang â Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumenthat the customer is entitled have reimbursement / restitution / compensation when receiving the goods or services that are not as they should be.